2008
DOI: 10.1152/physrev.00018.2006
|View full text |Cite
|
Sign up to set email alerts
|

Amino Acid Transport Across Mammalian Intestinal and Renal Epithelia

Abstract: The transport of amino acids in kidney and intestine is critical for the supply of amino acids to all tissues and the homeostasis of plasma amino acid levels. This is illustrated by a number of inherited disorders affecting amino acid transport in epithelial cells, such as cystinuria, lysinuric protein intolerance, Hartnup disorder, iminoglycinuria, dicarboxylic aminoaciduria, and some other less well-described disturbances of amino acid transport. The identification of most epithelial amino acid transporters … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

21
671
2
15

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 813 publications
(730 citation statements)
references
References 417 publications
21
671
2
15
Order By: Relevance
“…The amino acid analog MeAIB is an inhibitor and specific substrate for system A amino acid transport and the main transport mechanism for MeAIB uptake is thought to occur via system A [27][28][29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…The amino acid analog MeAIB is an inhibitor and specific substrate for system A amino acid transport and the main transport mechanism for MeAIB uptake is thought to occur via system A [27][28][29][30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism is unclear. Yet, 5-HTP could undergo active transport by large neutral amino-acid transporters present in the colon as well as in the upper intestine (Broer, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…herein]. The study of interaction of mercuric reagents with transport systems for glutamine is still at an initial stage, in spite of the essential role of these transporters in cell homeostasis [25]. It was reported that methylmercury modify the permeability to glutamine of cultured astrocytes by an indirect mechanism based on inhibition of expression of the amino acid transporters ASCT2 and SNAT3; however, this mechanism only partially explained the permeability alteration [26].…”
Section: Introductionmentioning
confidence: 99%
“…It was reported that methylmercury modify the permeability to glutamine of cultured astrocytes by an indirect mechanism based on inhibition of expression of the amino acid transporters ASCT2 and SNAT3; however, this mechanism only partially explained the permeability alteration [26]. The rat glutamine/amino acid transporter ASCT2 which is expressed in kidney, intestine and nervous system besides other tissues [25], was reconstituted in liposomes [27][28]. The transporter was inserted unidirectionally in the proteoliposomal membrane, right-side-out with respect to the cell membrane; thus, the properties of the internal side of the reconstituted transporter correspond to those of the intracellular side and vice versa.…”
Section: Introductionmentioning
confidence: 99%